TEACHERS’ PERCEPTION OF FACTORS RESPONSIBLE FOR ATTRITION OF TEACHERS IN PUBLIC SECONDARY SCHOOLS IN EDO CENTRAL SENATORIAL DISTRICT - Igbineweka, V O.; Orboh, Ehiaguina Sebastian (Sokoto Educational Review, 2011)
This study examined teachers' perception of factors responsible for the attrition of teachers in public secondary schools in Edo central senatorial district. Two hypotheses were raised to guide the investigation that adopted the survey research design. A sample size of 105participants was drawn from a population of 1,035 teachers in all the public secondary in Edo State. A research instrument titled: Factors of Attrition Questionnaire (FATAQUE) was used to collect data for the study. The t-test statistics was used to analyze the hypotheses. The result of the analysis showed that job satisfaction, morale and remuneration were perceived as factors responsible for attrition of teachers; the male teachers have a higher rating which probably makes them prone to attrition than their experienced folks. It was recommended that government and relevant stakeholders should help improve teacher’s level of job satisfaction, morale and remuneration.